Anemia and symptoms of depression in patients with early breast cancer at the National Institute of Neoplastic Diseases, Lima, Peru - Casavilca-Zambrano, Sandro (2022)
Objective. The aim of this study was to determine the relationship between anemia and depressive symptoms in patients with early stage breast cancer at the National Institute of Neoplastic Diseases (INEN), Lima, Peru. Methods. An analytical cross-sectional  observational study of 60 Peruvian women diagnosed with early stage I and II breast cancer was conducted between June 2019 and March 2020. All participants were assessed by Beck Depression Inventory-II (BDIII) score, had not received prior chemotherapy, and met the inclusion criteria. Each participant provided a blood sample that was used to estimate hemoglobin and red and white blood cell counts. Results. Of the 60 patients who met the inclusion criteria, twenty (33.3%) had depressive symptoms at the time of diagnosis. Mean hemoglobin levels in patients with depressive symptoms (M = 10.9, SD = 2.1) were lower compared to those in patients without depression (M = 13.6, SD =1, p =0.004). A limitation of our study was the small sample size and the fact that thyroid hormones and vitamin B12 were not tested. Conclusions. Our study found a significant difference in hemoglobin levels among breast cancer patients with symptoms of depression. Interventions to address the presence of anemia and depression in women with breast cancer are needed to improve health outcomes in these patients.